Evaluasi Program Praktik Kerja Industri dalam Rangka Meningkatkan Kompetensi, Kesiapan Kerja dan Karakter Islami Siswa di Sekolah Menengah Kejuruan: Evaluation of Industrial Internship Programs to Improve Students' Competence, Job Readiness and Islamic Character in Vocational High Schools - Fildya Rizki; Irja Eka Putri; Khaironita; Aisatun Nadroh; Arifmiboy (AJMIE: Alhikam Journal of Multidisciplinary Islamic Education, 2026)
This study aims to analyze the context, input, Process, and product aspects of the implementation of the Industrial Work Practice Program at SMKN 1 Lembah Melintang, West Pasaman Regency. This study uses a quantitative approach with a descriptive evaluative research type using the CIPP (Context, Input, Process, Product) evaluation model. The research data were obtained through distributing questionnaires to 126 respondents consisting of students, supervising teachers, principals, and DUDI (Industrial and Industrial Business World) parties. The data were analyzed using quantitative descriptive analysis techniques with percentages. The results showed that the evaluation of the context aspect obtained a percentage of 78.82% with a good category, the input aspect was 74.20% with a good category, the Process aspect was 74.01% with a good category, and the product aspect was 73.45% with a good category. Based on these results, it can be concluded that the implementation of the PKL Program at SMKN 1 Lembah Melintang, West Pasaman Regency has been running well and is able to support the improvement of students' competencies and work readiness as well as the development of students' Islamic character, although some improvements are still needed in the aspects of monitoring and coordination with the Business World and Industry (DUDI)